2015
DOI: 10.1002/14651858.cd010472.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Device-modified trabeculectomy for glaucoma

Abstract: Background-Glaucoma is an optic neuropathy that leads to vision loss and blindness. It is the second most common cause of irreversible blindness worldwide. The main treatment for glaucoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…While risk factors of glaucoma and other optic neuropathies including age, genetic and epigenetic variants, as well as sensitivity to elevated intra-ocular pressure (IOP) have been studied extensively, IOP to date remains the only clinically manageable factor. 2 Nevertheless, 40%–50% of certain patient populations continue to progress toward blindness despite treatment, and many others only clinically present with advanced stages of disease, exposing the inability of current treatments to recover already-lost vision. 3 Hence, further therapeutic routes are currently being explored, including neuroprotection, gene therapy, and cell replacement.…”
Section: Introductionmentioning
confidence: 99%
“…While risk factors of glaucoma and other optic neuropathies including age, genetic and epigenetic variants, as well as sensitivity to elevated intra-ocular pressure (IOP) have been studied extensively, IOP to date remains the only clinically manageable factor. 2 Nevertheless, 40%–50% of certain patient populations continue to progress toward blindness despite treatment, and many others only clinically present with advanced stages of disease, exposing the inability of current treatments to recover already-lost vision. 3 Hence, further therapeutic routes are currently being explored, including neuroprotection, gene therapy, and cell replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Modified trabeculectomies in which devices are used to control outflow or to modify healing and promote continued drainage from the anterior chamber are not considered aqueous shunts for the purposes of this review. A separate Cochrane review identified low-certainty evidence suggesting that these devices used with standard trabeculectomies may help reduce IOP (Wang 2015). Examples of these modified trabeculectomies include the EX-PRESS shunt, Ologen implant, SKgel implant, and T-flux implant.…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 Cochrane Review examined eight clinical trials published up to December 2014 assessing the use of Ologen™ implant in trabeculectomy compared with MMC. 12 25 - 30 The meta-analysis, which studied a total of 333 eyes of 327 participants, concluded that due to low-quality evidence, there is uncertainty whether there is a significant difference in outcomes (including IOP reduction and best-corrected visual acuity) or adverse events between the Ologen™ and MMC groups. 30 …”
Section: Adjunct Tools For Conventional Glaucoma Surgerymentioning
confidence: 99%
“…The review labeled the aggregation of data as low quality, but concluded that AMT may slightly improve IOP reduction and lead to slightly less frequent complications compared with standard trabeculectomy. 30 Sheha et al, 69 in a randomized prospective study of 37 eyes, compared trabeculectomy with MMC (control) to trabeculectomy with MMC and AMT (study group) and found that AMT had higher success rates, lower postoperative mean IOPs, and fewer complications. Khairy and Elsawy 70 presented another prospective randomized controlled comparison trial of 52 eyes with trabeculectomy with MMC or with AMT.…”
Section: Adjunct Tools For Conventional Glaucoma Surgerymentioning
confidence: 99%